6 - Compromised Co-management, Compromised Outcomes: Experiences from a Zimbabwean Forest - Mapedza, Everisto (Africa Development, 2006)
Zimbabwe embarked on decentralisation of forestry resources after the ‘success’ of devolved management of wildlife through the Communal Areas Management Programme for Indigenous Resources (CAMPFIRE). This paper examines the outcomes of the introduction of co-management in the Mafungautsi Forest in Zimbabwe. Decentralisation reforms of 1984 introduced new institutional arrangements, which resulted in a shift in the power loci and relationships. However, co-management in the Mafungautsi has not devolved meaningful powers to these new institutions, making them more accountable to the forestry department than they are towards their constituencies. In the Mafungautsi, this has had the result of outcomes counter to those for which the programme was implemented. The results from the Mafungautsi case study in Zimbabwe dem- onstrate that a decentralisation reform that establishes institutions that are up- wardly accountable to the centre will more likely result in negative social, eco- nomic, and environmental outcomes.